Rapid microwave-assisted biomass delignification and lignin depolymerization in deep eutectic solvents. (15th September 2019) - Muley, Pranjali D.; Mobley, Justin K.; Tong, Xinjie; Novak, Brian; Stevens, Joseph; Moldovan, Dorel; Shi, Jian; Boldor, Dorin
Highlights: Deep eutectic solvents was used for biomass and lignin depolymerization. Oxalic acid and formic acid DES gave the highest lignin yields. Microwave heating promoted selective bond cleavage during lignin depolymerization. MD simulations show that certain bonds stretch more during microwave irradiation. Abstract: Biomass deconstruction and lignin depolymerization was performed using three different deep eutectic solvents. Various temperature (110°, 130°, and 150 °C) and time (1, 5, 10, 15 min) conditions were tested in a 2450 MHz microwave reactor. Oxalic acid (130 °C, 15 min) and formic acid DES (150 °C, 15 min) gave the highest lignin yield. Microwave heating reduced the processing time significantly. NMR characterization shows that microwave heating promotes selective bond cleavage during lignin depolymerization and has a narrow molecular weight distribution compared to conventional heating techniques. Molecular dynamic simulations showed that certain lignin bonds are stretched under the electric field imparted during microwave irradiation, increasing its probability of breaking.